Analisis Sistem Penghargaan dan Beban Kerja terhadap Kinerja Perawat Pelaksana Rumah Sakit pada Masa Pandemi COVID -19 - Ismar Agustin; Muliyadi Muliyadi; Mutia Nadra Maulida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine whether rewards and workload affect the performance of nurses in inpatient services at a hospital in Palembang City. This research is included in the category of ex-post-facto study and is also causally associative. The results showed that most of the nurses had vocational education (D III Nursing) with 100 nurses (74.6%), female 116 (86.6%), married 112 (83.4%), and permanent employment status 40 ( 29.9%) followed by Honor/contract/non-permanent 39 (29.1%). The analysis results obtained a p-value of 0.048 for the nurse workload variable with nurse performance and a p-value of 0.035 <0.05 for the reward system and nurse performance. In conclusion, there is a significant relationship between the reward system and version, and there is a substantial relationship between workload and performance. Keywords: workload, performance, nurses, reward system